2009
DOI: 10.1111/j.1529-8817.2009.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC DIVERSITY AND INTROGRESSION IN TWO CULTIVATED SPECIES (PORPHYRA YEZOENSISANDPORPHYRA TENERA) AND CLOSELY RELATED WILD SPECIES OFPORPHYRA(BANGIALES, RHODOPHYTA)1

Abstract: We investigated the genetic variations of the samples that were tentatively identified as two cultivated Porphyra species (Porphyra yezoensis Ueda and Porphyra tenera Kjellm.) from various natural populations in Japan using molecular analyses of plastid and nuclear DNA. From PCR-RFLP analyses using nuclear internal transcribed spacer (ITS) rDNA and plastid RUBISCO spacer regions and phylogenetic analyses using plastid rbcL and nuclear ITS-1 rDNA sequences, our samples from natural populations of P. yezoensis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 36 publications
0
68
0
Order By: Relevance
“…In practice, species can thus be identified if gene genealogies of multiple unlinked loci show congruent patterns of reciprocal monophyly (Taylor et al, 2000;Dettman et al, 2003). The criteria of reciprocal monophyly and genealogical concordance of unlinked loci has been widely used (although not always explicitly) to delimit algal species (Casteleyn et al, 2008;Sherwood et al, 2008;Fraser et al, 2010;Škaloud & Peksa, 2010;Lundholm et al, 2012;Schmidt et al, 2012;Rybalka et al, 2013;Škaloud & Rindi, 2013), even if some of these studies showed possible signals of hybridization and/or introgression, blurring species boundaries Lane et al, 2007;Niwa et al, 2009;Destombe et al, 2010;Hind & Saunders, 2013). Genealogical concordance of unlinked, neutral loci is expected among well-diverged lineages.…”
Section: Multi-locus Species Delimitationmentioning
confidence: 99%
“…In practice, species can thus be identified if gene genealogies of multiple unlinked loci show congruent patterns of reciprocal monophyly (Taylor et al, 2000;Dettman et al, 2003). The criteria of reciprocal monophyly and genealogical concordance of unlinked loci has been widely used (although not always explicitly) to delimit algal species (Casteleyn et al, 2008;Sherwood et al, 2008;Fraser et al, 2010;Škaloud & Peksa, 2010;Lundholm et al, 2012;Schmidt et al, 2012;Rybalka et al, 2013;Škaloud & Rindi, 2013), even if some of these studies showed possible signals of hybridization and/or introgression, blurring species boundaries Lane et al, 2007;Niwa et al, 2009;Destombe et al, 2010;Hind & Saunders, 2013). Genealogical concordance of unlinked, neutral loci is expected among well-diverged lineages.…”
Section: Multi-locus Species Delimitationmentioning
confidence: 99%
“…(4) It is still unclear about geographic origination, molecular characterization and anthropogenic disturbance of various P. yezoensis cultivars as genetic resources from the viewpoint of global commercial utilization. Several molecular studies have identified the cultivated and wild strains of P. yezoensis through detecting genetic divergence (Kunimoto et al , 2003Mizukami et al 1999;Niwa and Aruga 2006;Niwa et al 2009), but so far no clear clarification presented among all cultivated and wild strains of P. yezoensis throughout the world. In order to keep and advance the development of nori breeding, it is a pressing task to unambiguously and correctly elucidate the network relationships for most commonly used various P. yezoensis strains.…”
Section: Introductionmentioning
confidence: 98%
“…In this genus, cultivated P. yezoensis Ueda is one of the most economically important marine crops in East Asia (Niwa and Aruga 2003;Niwa et al 2008). Since the 1960s with the development of synthetic fiber nets, strain-preservation and artificial seeding in Porphyra mariculture, nearly 60 strains of P. yezoensis have been isolated and used for cultivation in Japan, China and South Korea Iitsuka et al 2002;Hwang et al 2005;Weng et al 2005;Hu et al 2007;Niwa et al 2008Niwa et al , 2009. Although these cultivars have considerably contributed to increasing yields, some subsequent problems occurred in nori farms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical to develop local cultivars and cultivation techniques suitable for the local environments and boutique markets. Selective breeding (intra-specific and inter-specific) of cultivated Pyropia/Porphyra has been intensively studied in Asia (Miura 1984;Shin 1999Shin , 2003Niwa et al 2009). Genetic improvement has resulted in superior strains with higher growth rates, better flavor, darker color and higher tolerance to diseases (Chen et al 2014).…”
Section: Red Seaweedsmentioning
confidence: 99%